Are we on track with sustainability literacy?: A viewpoint on the influence of sustainability and accounting education on future managers' processing of sustainability information. Issue 1 (6th May 2014) - Hahn, Rüdiger; Reimsbach, Daniel
Abstract : Purpose: – In this viewpoint, the authors aim to discuss sustainability issues in university education. Balancing what we call the "Accounting View" and the "Sustainability View", the authors illuminate the status of value relevance of sustainability information and question the depth of business students' processing of this information. Design/methodology/approach: – The discussion was triggered by an experimental study on sustainability disclosure which revealed interesting findings related to the participating students' prior sustainability and accounting coursework. The authors start the viewpoint from these findings and contrast them with existing views on sustainability and accounting (education). Findings: – The amount of accounting coursework was positively related to the probability of including sustainability information in future stock value estimates, whereas this applied only marginally to sustainability coursework. However, students with more sophisticated sustainability knowledge seemed to scrutinize the given sustainability information more deeply, while students with "pure" accounting knowledge seemed more willing to simply accept the information. Practical implications: – The authors argue for advancements in the curriculum for business students that foster critical thinking and might prevent students (and thus potential future managers) from using sustainability information superficially. The authors caution against regarding sustainability issues as an "add-on" to existing courses and curricula and call for a combination of integrating sustainability issues in (core) business courses and offering standalone courses on sustainability management or CSR. Originality/value: – Triggered by findings from an experimental study, the authors contrast different opinions on sustainability education of business students and offer a new viewpoint on the (supposed) value relevance of sustainability information for future business leaders.